Eksistensi Kedaulatan Kreditor Konkuren dalam Perdamaian melalui PKPU yang Berkeadilan : (Studi Putusan: Nomor 751 K/Pdt.Sus-Pailit/2024) - Brigita Natalia Rose Santi; Adi Sulistiyono (Pusat Riset dan Inovasi Nasional, 2025)
Postponement of Debt Payment Obligations (PKPU) is a legal mechanism that provides an opportunity for creditors and debtors to submit a debt reschedule plan to avoid bankruptcy. In the PKPU process, creditors have a role in determining the success of the agreement. In this case, concurrent creditors are more advantaged, because their position can be equal to that of separatist creditors who have collateral. This study examines how the existence of concurrent creditor sovereignty in the agreement process through PKPU, and to what extent the regulations regarding concurrent creditors and their rights are benefited in the cassation decision, especially in the Supreme Court Decision Number 751 K /Pdt.Sus-Pailit/2024. This research is a normative legal research, with prescriptive legal approach and conceptual approach. The types of data used include primary and secondary legal materials, which are collected through literature studies. The legal material analysis technique uses the syllogism and interpretation methods. The results of the analysis, this study identifies how the protection of concurrent creditor sovereignty in peace through PKPU. And how the Supreme Court Decision in Decision No. 751 K/Pdt.Sus-Pailit/2024 pays more attention to concurrent creditors. In this discussion, shows how the regulations and legal protection of concurrent creditors, while discussing the Supreme Court Decision No. 751 K/Pdt.Sus-Pailit/2024 which gave rise to polemics in the interpretation of the provisions of Article 281 paragraph 1. However, it is likely to reflect the judiciary in considering all creditors and debtors, to achieve equal justice for all parties.